If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(x + 6) + -10 = 2(5 + 4x) Reorder the terms: -6(6 + x) + -10 = 2(5 + 4x) (6 * -6 + x * -6) + -10 = 2(5 + 4x) (-36 + -6x) + -10 = 2(5 + 4x) Reorder the terms: -36 + -10 + -6x = 2(5 + 4x) Combine like terms: -36 + -10 = -46 -46 + -6x = 2(5 + 4x) -46 + -6x = (5 * 2 + 4x * 2) -46 + -6x = (10 + 8x) Solving -46 + -6x = 10 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -46 + -6x + -8x = 10 + 8x + -8x Combine like terms: -6x + -8x = -14x -46 + -14x = 10 + 8x + -8x Combine like terms: 8x + -8x = 0 -46 + -14x = 10 + 0 -46 + -14x = 10 Add '46' to each side of the equation. -46 + 46 + -14x = 10 + 46 Combine like terms: -46 + 46 = 0 0 + -14x = 10 + 46 -14x = 10 + 46 Combine like terms: 10 + 46 = 56 -14x = 56 Divide each side by '-14'. x = -4 Simplifying x = -4
| 11a+9= | | 6=x/2-9 | | 3x^(2/3)-x^(1/3)-1=0 | | x+12=53 | | x+56=452 | | 10(2)+11(2)=c(2) | | v(x)=x^3-4x^2-4x | | 7y-5=2y+8 | | 5x+2=563 | | 16uv=8uw | | 17f=44 | | z^3+5z+12iz=0 | | 5×2/7 | | 9/7÷3/4 | | X^2-c-110=0 | | (x+5y)(5x+2y)=0 | | 5a*3-4a+9= | | 8X+5(210-X)=3150 | | 5/9=x/123 | | 0.4y+3.9=5.78 | | 5x+2(x+3)-4x=4(x+1)-(x-2) | | (x-6)/6=3/8 | | 1+2iz=3-5i | | 4a+7b+5a+b= | | 4x-3+8=7x | | 7X+4(25-X)=400 | | 5x+78=180 | | 5(f+9)-13=12f+8-7f | | 50=-16x^2+80x+5 | | 6x-4=13-74 | | 10c+7=32 | | 4(z-2)+3(4+4)=-12 |